Penerapan Model Problem Based Learning (PBL) Materi Perubahan Bentuk Energi Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas IV UPTD SD Negeri 64 Parepare - Israwaty, Ila; Usman, Usman; Asrullah, Asrullah (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The problem in this study is the low learning motivation of students in the subject of science. This study aims to determine the process and results of the application of the Problem Based Learning (PBL) learning model to improve the learning motivation of fourth-grade students of UPTD SD Negeri 64 Parepare. This study uses a qualitative approach with the classroom action research (CAR) method. Data collection techniques used are observation, questionnaires and documentation, with research subjects consisting of 1 teacher and 16 students. This study was conducted in two cycles, each cycle consisting of two meetings covering planning, implementation, observation, and reflection. The results of the study showed that in cycle I, the learning process was in the sufficient qualification (C) and the learning motivation of students was in the sufficient learning motivation category. In cycle II, the results of the study on the learning process were in the good qualification (B) and the learning motivation of students reached the high learning motivation category. The conclusion in this study is that the application of the Problem Based Learning (PBL) learning model can improve the learning motivation of students in the learning of fourth-grade science at UPTD SD Negeri 64 Parepare.